Pengaruh Slow Stroke Back Massage Terhadap Fatigue : Literature Review - Kiranti Ayu Safitri; Thomas Ari Wibowo (Borneo Student Research (BSR), 2022)
Tujuan studi: Tujuan dari penelitian ini yaitu mengetahui apakah ada pengaruh slow stroke back massage dengan keluhan fatigue. Metodologi : Metode yang digunakan adalah Literature Review dengan databesed pencarian seperti Google Scholar, Sage, Science Direct, dan Pubmed, Jurnal yang digunakan ada 15 terdiri dari 5 jurnal Nasional dan 10 Internasional yang sesuai dengan Kriteria Inklusi. Hasil:Hasil dari pembahasan analisis Literature Review bahwa slow stroke back massage mampu untuk menurunkan pasien dengan keluhan fatigue. Manfaat: Hasil dari penelitian ini diharapkan agar slow stroke back massage mampu untuk mengatasi keluhan pasien dengan fatigue. Abstract Purpose of study: The purpose of this study was to determine whether there was an effect of slow stroke back massage with complaints of fatigue. Methodology: The method used is Literature Review with database searches such as Google Scholar, Sage, Science Direct, and Pubmed. The journals used are 15 consisting of 5 National and 10 International journals that comply with the Inclusion Criteria. Results: The results of the discussion of the Literature Review analysis that slow stroke back massage is able to reduce patients with complaints of fatigue. Applications: The results of this study are expected that slow stroke back massage is able to overcome thecomplaints of patients with fatigue.